Peluang dan Kendala Pengembangan LKM dalam Membiayai Permodalan UMKM di Kabupaten Seluma - Barika Barika; Antoni Sitorus (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2019)
The study aims to identify opportunities and constraints for the development of microfinance institutions (MFIs) in Seluma district. Formulate a development strategy for microfinance institutions in the future. The method used in this research is descriptive method. The approach used in this study is a quantitative approach. The type of data used in this study is primary data and secondary data. Primary data is obtained through direct interviews with research respondents, namely MSME actors in the trade sector in Kab seluma by giving questions that have been compiled in the questionnaire. While secondary data was obtained from the relevant agencies in the study, namely the Central Bureau of Statistics, Department of Animal Husbandry as well as reports of previous research results as well as data from internet browsing. The results showed that there were several opportunities in the development of MFIs, among others, the high participation of members in repaying loans, the low level of bad loans, the closeness between the management and members of the MFI and there was an increase in members' business performance. The constraints in developing MFIs include the low level of collaboration with the banking sector and the low capital of the MFI itself.